PREVALENCE OF HUMAN ADENOVIRUS IN PAEDIATRIC PATIENTS PRESENTING WITH ACUTE RESPIRATORY SYMPTOMS AT DIFFERENT HOSPITALS OF PAKISTAN - Shahzad Ahmad,; Arshad Malik,; Ullah, Ihsan; Nazish Badar,; Ishaq N Khan,; Amir Atlis,; Anees Muhammad,; Muhammad Uzair Khan, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Human Adenovirus (HAdV) is one of the most common causes of infection in children. HAdV commonly affects respiratory system, however can also involve other parts of the body like nervous system, eyes and urinary tract. The virus usually causes a mild infection of the lower and upper respiratory tract. Objective of the study was to find the prevalence of HAdV in paediatric patients presenting with Influenza like symptoms and severe acute respiratory illness across Pakistan. Methods: This cross-sectional study was conducted at the National Institute of Health, Islamabad. Respiratory swabs were collected from 389 children with age less than five years from 14 hospitals in different regions of Pakistan from October 1, 2017 to September 30, 2018. Patients' demographics, signs and symptoms were recorded through a predesigned proforma while Real-time polymerase chain reaction (RT-PCR) was performed for respiratory samples. Results: Out of all 389 samples, HAdV was found in 25 (6.4%) cases. The proportion of HAdV obtained was greater in females 18 (4.6%) than male 7 (1.8%). The influenza-like illness in children attending outpatient department had a higher prevalence of HAdV 13(3.3%) compared to admitted children 12 (3.1%). Similarly, patients from one to 6 months of age had higher positive outcome than older children. Majority of positive patients were from Islamabad (2.0%) followed by Gilgit (1.8%), Azad Jammu Kashmir (1.0%), Multan (0.5%), and Karachi (0.5%). The most frequent signs and symptoms were cough, fever, sore throat, nasal congestion and shortness of breath. Conclusion: The present study concludes that HAdV infection is common in Pakistan especially in female patients aged 1-6 months. It's crucial to improve the diagnosis of HAdV infections in our country to prevent complications associated with the virus. Furthermore, genetic analysis may help find different genotypes of HAdV circulating in Pakistan.